Paper 2: Performing rapid reviews - Valerie J. King; Adrienne Stevens; Barbara Nussbaumer-Streit; Chris Kamel; Chantelle Garritty (Systematic Reviews, 2022)
Abstract Background Health policy-makers must often make decisions in compressed time frames and with limited resources. Hence, rapid reviews have become a pragmatic alternative to comprehensive systematic reviews. However, it is important that rapid review methods remain rigorous to support good policy development and decisions. There is currently little evidence about which streamlined steps in a rapid review are less likely to introduce unacceptable levels of uncertainty while still producing a product that remains useful to policy-makers. Methods This paper summarizes current research describing commonly used methods and practices that are used to conduct rapid reviews and presents key considerations and options to guide methodological choices for a rapid review. Results The most important step for a rapid review is for an experienced research team to have early and ongoing engagement with the people who have requested the review. A clear research protocol, derived from a needs assessment conducted with the requester, serves to focus the review, defines the scope of the rapid review, and guides all subsequent steps. Common recommendations for rapid review methods include tailoring the literature search in terms of databases, dates, and languages. Researchers can consider using a staged search to locate high-quality systematic reviews and then subsequently published primary studies. The approaches used for study screening and selection, data extraction, and risk-of-bias assessment should be tailored to the topic, researcher experience, and available resources. Many rapid reviews use a single reviewer for study selection, risk-of-bias assessment, or data abstraction, sometimes with partial or full verification by a second reviewer. Rapid reviews usually use a descriptive synthesis method rather than quantitative meta-analysis. Use of brief report templates and standardized production methods helps to speed final report publication. Conclusions Researchers conducting rapid reviews need to make transparent methodological choices, informed by stakeholder input, to ensure that rapid reviews meet their intended purpose. Transparency is critical because it is unclear how or how much streamlined methods can bias the conclusions of reviews. There are not yet internationally accepted standards for conducting or reporting rapid reviews. Thus, this article proposes interim guidance for researchers who are increasingly employing these methods.